1991
DOI: 10.3354/dao010065
|View full text |Cite
|
Sign up to set email alerts
|

Encephalomyelitis among turbot associated with a picornavirus-like agent

Abstract: An outbreak of encephalomyelitis among larval turbot ScophthaLmus maximus caused very heavy mortalities. Bacteriological findings were very unspecific, and parasites were not observed. By electron microscopy large numbers of virus particles were found in the brain and medulla of the diseased fish. Based on the size of the particles and their position in the cytoplasm of the infected cells it is suggested that the particles belong to the picomaviridae. The neurotropic character of the disease further suggests t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0
6

Year Published

1992
1992
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(92 citation statements)
references
References 10 publications
2
84
0
6
Order By: Relevance
“…Uncoordinated swimming, i.e. spiral swimming and darting, although flatfish tend to have a looping swimming pattern and to rest belly up were reported by [3,[15][16][17][18][19][20][21]. Similar clinical signs were reported during serious mortalities affecting Grey mullet in Iranian coastal water of the Caspian Sea [1,22].…”
Section: Discussionmentioning
confidence: 82%
“…Uncoordinated swimming, i.e. spiral swimming and darting, although flatfish tend to have a looping swimming pattern and to rest belly up were reported by [3,[15][16][17][18][19][20][21]. Similar clinical signs were reported during serious mortalities affecting Grey mullet in Iranian coastal water of the Caspian Sea [1,22].…”
Section: Discussionmentioning
confidence: 82%
“…The infections are also reported in hatchery-reared Japanese parrotfish, Oplegnathus fasciatus in Japan [122] and Barramundi larvae (L. calcarifer) in Australia [42]. Several reports are also documented from turbot Scophthalmus maximus [12], European seabass D. labrax [13] redspotted grouper Epinephelus akaara [80], and striped jack Pseudocaranx dentex [81]. The infections can occur in a variety of cultured warm water and cold water marine fish species [83,86] as well as some fresh water fish [52,53].…”
Section: Introductionmentioning
confidence: 87%
“…The RNA1 segment encodes two non-structural viral replicase proteins, while the RNA2 encodes the structural capsid protein. The disease has been reported by a variety of names such as viral nerve necrosis (VNN) [122], fish encephalitis virus [12] and viral encephalopathy and retinopathy [83,93]. The virus is found to be affecting both cold water and warm water fishes and reported throughout the world [83].…”
Section: Aetiologymentioning
confidence: 99%
“…In recent years, a viral disease similar to "viral nervous necrosis" of Japanese parrotfish Op legnathus fasciatus (Yoshikoshi and Inoue, 1990) or "encephalomyelitis" of turbot Scophthalmus maximus (Bloch et al, 1991) has been reported in hatchery-reared larvae and juveniles of bar ramundi Lates calcarifer, sea bass Dicentrarchus labrax, redspotted grouper Epinephelus akaara, and striped jack Pseudocaranx dentex in several countries (Glazebrook et al, 1990;Renault et al, 1991;Breuil et al, 1991;Mori et al, 1991Mori et al, , 1992. Although Koch's postulates on viral etiology were not fulfilled in these disease cases except for redspotted grouper (Mori et al, 1991) and the putative causative viruses have not been isolated in fish cell lines, all of them seem to have a similar viral etiology.…”
Section: Toshihiromentioning
confidence: 99%